Disability, society, and theology : voices from Africa - Kabue, Samuel (Limuru, Kenya : Zapf Chancery Publishers Africa, 2011)
Disability, Society and Theology: Voices from Africa is the result of a workshop which brought together African theologians, persons with disabilities and disability expertise in the Region to prepare resource materials to enrich the disability study process in the context of the Africa region. The book is in six parts and includes contributions from scholars across the continent. The parts are: Disability Theology: Issue to Debate; The Able Disabled and the Disabled Church: The Church's Response to Disability; Disability and Society; Disability Theology: Some Interfaces; Disability and Caregiving; and Disability in the African Experience.
Persons with disabilities in church and society : a historical and sociological perspective / Samuel Kabue -- Claiming and developing a disability hermeneutics : toward a liberating theology of disability / Arne Fritzson -- Perfect God and imperfect creation : in the image of God and disabled / Joseph D. Galgalo -- Sin, suffering, and disability in God's world / A. Wati Longchar -- One in Christ : priesthood of the disabled and the exercising of gifts / C.B. Peter -- Biblical perspectives on disability / Sammy Githuku -- Lazarus, come out! : how contextual Bible study can empower the disabled / Janet Lees -- The Church, public policy, and disability concerns in Kenya / Phitalis Were Masakhwe -- Cultural barriers to the disabled people's participation in church life / Reuben Kigame -- Education, employment, and health : a disability perspective / Anjeline Okola -- Society and leadership : challenges and opportunities for people with disabilities / Esther Mombo -- Disability : social challenges and family responses / Joseph Shiriko -- Disability and sexuality / Salome Wairimu Muigai -- Combating HIV & Aids among persons with disability : a disability perspective / Paul Chappell -- Persons with disabilities and psychological perspectives / Ndung'u J.B. Ikenye -- Psychosocial disability : attitudes and barriers to social integration in church and society / Janet Amegatcher -- The Church and pastoral counseling for disability / David Kiarie -- Persons with disabilities in Madagascar / Ralphine Razaka -- Persons with disabilities in Malawi : what are the issues? / Rachel Kamchacha Kachaje -- A profile of Tanzanians with disabilities / Kaganzi Rutachwamagyo -- Persons with disabilities in Uganda / Gidudu Balayo N. Seezi -- Persons with disability in South Africa / Joy Sebenzile & P. Matsebula.
Papers from a workshop held in 2008 at St. Paul's University, Limuru, Kenya.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 072
Keywords: Disabilities -- Religious aspects -- Christianity -- Congresses; Sociology of disability -- Africa -- Congresses; RELIGION -- Christian Life -- Social Issues; RELIGION -- Christianity -- General; Sociology of disability; Africa; SOCIAL SCIENCE / People with Disabilities; Electronic books; Conference papers and proceedings